Size and Shape Design Optimization of Truss Structures Using the Jaya Algorithm - Grzywiński, Maksym (Computer Assisted Methods in Engineering and Science, 2020)
The metaheuristic algorithm is proposed to solve the weight minimization problem of truss structures, considering the shape and sizing design variables. Design variables are discrete and/or continuous. The design of truss structures is optimized by an efficient optimization algorithm called Jaya. The main feature of Jaya is that it does not require setting algorithm-specific parameters. The algorithm has a very simple formulation in which the basic idea is to approach the best solution and escape from the worst solution [6]. Analyses of structures are performed by a finite element code in MATLAB. The effectiveness of the Jaya algorithm is demonstrated using two benchmark examples: planar truss 18-bar and spatial truss 39-bar, and compared with results in references.